The Influence of the Implementation of the Hospital Management Information System (SIMRS) on the Effectiveness of Patient Administration Services at Grandmed Hospital Lubuk Pakam - Aya Sofia Diaz (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Hospital Management Information System (SIMRS) is an information technology-based system designed to manage all aspects of hospital operations and administration in an integrated and efficient manner. In the context of administrative services, SIMRS plays an important role in accelerating the registration process, increasing the accuracy of data recording, and facilitating access to information across service units. This study aims to evaluate the effect of SIMRS implementation on the effectiveness of patient administration services at Grandmed Lubuk Pakam Hospital. This study uses a quantitative approach with a cross-sectional design. The sample consisted of 96 respondents, including administrative officers and patients, who were selected by purposive sampling. Data were collected using a closed questionnaire that had been tested for validity and reliability, then analyzed using the chi-square test with the help of SPSS version 18 software. The results showed that there was a significant relationship between SIMRS implementation and increased effectiveness in four main indicators, namely speed of service, data accuracy, ease of access to information, and patient satisfaction. These findings